Aide-memoire, 1943-1954 : boyhood in British India and Pakistan - Hye, Hasnat Abdul (Dhaka : Adorn Publication, 2008)
Childhood memoirs of a Bengali author and civil servant from Bangladesh.
1. 1943-1954: boyhood in British India and Pakistan -- 2. 1954-1964: youth in Pakistan, America, Europe.
Donated by Rebecca Dipa Khan
Keywords: Hye, Hasnat Abdul -- Childhood and youth; Authors, Bengali -- Bangladesh -- Biography; Civil service -- Bangladesh -- Biography